Mathematical simulation for the assessment of clinical efficacy of the treatment of hypertensive crisis - Vdovichenko, V P; Snezhinskiĭ, V A (Klinicheskaia meditsina, 2009)
Retrospective analysis included case histories of 182 patients with hypertensive disorders and one or more crises (HC). The aim was to study the relationship between drug therapy and occurrence of HC. As known, clinical diagnosis of hypertensive disorder dictates therapeutic strategy for AH. It was shown that diagnosis of neurocirculary dystonia (asthenia) prevented timely prescription antihypertensive treatment and resulted in HC. Mathematical simulation of anti-AH therapy in the presence of HC allows patients at high risk of stroke to be identified for follow-up and adequate treatment.